No Evidence That Sound–Shape Associations Influence Temporal Resolution in Humans: Five Nonreplications of Parise and Spence (2009) and Meta-Analyses. - Sourav, Suddha; Röder, Brigitte; Ambsdorf, Franka; Melissari, Andromachi; Arvaniti, Miketa; Vatakis, Argiro (Journal of Experimental Psychology. General, 2025)
Sound–shape associations (e.g., preferentially matching angular shapes with high-pitched sounds and smooth shapes with low-pitched ones) have been almost universally observed in humans. If cross-modally congruent sounds and shapes are more robustly integrated in humans, distinguishing them in time might be hypothetically more challenging compared to incongruent sound–shape pairings. Supporting this premise, a highly cited work by Parise and Spence (2009; n = 12) reported worse temporal order judgement performance for audiovisual stimuli with congruent compared to incongruent sound–shape associations. Here, we report the results of five experiments across two laboratories, including a preregistered replication attempt, all (∑n = 102) failing to replicate the original results. Additionally, frequentist and Bayesian meta-analyses found no evidence against the null hypothesis, revealing a negligible effect size. The combined results indicate that multisensory temporal resolution in humans is unaffected by sound–shape associations, which might arise at a later (or parallel) processing stage compared to cross-modal temporal order judgements. Public Significance Statement: Humans generally associate arbitrary shapes and sounds in a similar way—for example, most people preferentially match the meaningless names "Bouba" and "Kiki" with smooth and spiky shapes, respectively. An influential study by Parise and Spence (2009) reported that sounds and shapes that go well together were more difficult to tell apart in time compared to sounds and shapes that did not match. Does sound–shape association really bind auditory and visual events stronger in time? In five replication experiments across two labs with more than a hundred participants (totaling more than eight times the sample size of the original study), we surprisingly found no evidence for this claim. These results argue that the timekeeping mechanisms that help us distinguish events across the auditory and the visual senses are not influenced by sound–shape associations.